EVALUASI KERAGAMAN FENOTIPE GALUR MUTAN PISANG BARANGAN {Mmaparadisiaca kuitivar Berangan) PADA GENERASI M, V4 - Dewi, Azri Kusuma; Dwimahyani, lta (BERITA BIOLOGI, 2005)
Phenotypic variance derived from banana [Musa paradisiaca) mutant lines of cv. Barangan were carried out in nursery level which were conducted at CRDIRT-Green House, Pasar Jumat, Jakarta. Several phenotypic performances of mutant lines such as leaf and pseudostem, petiole and leaf length, plant height, leaf width were observed. Number of 150 plants, were then divided into 11 groups based on performance of leaf, pseudostem, and petiole length. Results indicated that 26% was showed for normal performance,while 6,7% was showed for abnormal lamina with normal petiole, 11,3% was showed for abnormal lamina and petiole, 28,7% was given for stunted plant, 3,3% with chocking lamina, 1,3% was showed for abnormal petiole, 2,0% with light green leaf and abnormal petiole, 6,0% was given for reddish pseudostem, 0,7% with cigar leaf, 1,3% was showed for discoloration leaf and 2,7% was showed for elongation leaf and abnormal petiole. From the result of this experiment can be concluded that gamma irradiation with dose 15 Gy produced high phenotypic variance of cv. Barangan.